2021
DOI: 10.1002/jcla.23765
|View full text |Cite
|
Sign up to set email alerts
|

The potential diagnosis role of TP53 mutation in advanced bladder cancer: A meta‐analysis

Abstract: Background Bladder cancer is one of the most common urological cancers all over the world, and NMIBC occupies almost 80% of recently diagnosed bladder cancer cases. Progress and recurrence of bladder cancer are the main problems during the disease. The level of TP53 mutation is obviously higher in the high stage than the lower. This meta‐analysis is to evaluate the potential diagnosis feature of TP53 mutation by the expression of TP53 mutation of Ta stage vs high stage in bladder cancer. Methods A systematic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…In this study, p53 was overexpressed in urothelial carcinoma and its levels were higher in high-stage, high-grade, muscle-invasive, and metastatic disease. Those results are consistent with the recent meta-analysis published by Liao et al and reports regarding the prognostic value of p53 in NMIBC [ 31 , 32 ]. TP53 mutation is more frequent in muscle-invasive tumors when compared to non-invasive tumors (35 vs 70%), and correlates with tumor grade, stage, and disease recurrence [ 33 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, p53 was overexpressed in urothelial carcinoma and its levels were higher in high-stage, high-grade, muscle-invasive, and metastatic disease. Those results are consistent with the recent meta-analysis published by Liao et al and reports regarding the prognostic value of p53 in NMIBC [ 31 , 32 ]. TP53 mutation is more frequent in muscle-invasive tumors when compared to non-invasive tumors (35 vs 70%), and correlates with tumor grade, stage, and disease recurrence [ 33 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…The above ndings matched those ofLiao et al, 2021 who that high stage of BC has obviously higher level of TP53 mutation than the lower stage and also consistent with those ofShao et al, 2021 who reported that TP53 mutations were most frequent among BC patients with high tumor grade. The overall analysis provides a strong support to the initial ndings, which further con rmed the potential diagnosis role of TP53 mutation in advanced BC.The occurrence or recurrence of BC is a molecular biological change or process that is effected by occupational factors, non-occupational factors, genomics and proteomics factors(Fan, et al, 2021).The value of TP53 in bladder cancer as a predictive marker of tumor recurrence and treatment selection is still in debate(Sobhani et al, 2021).…”
supporting
confidence: 88%
“…It has been reported that various cell cycle modulators, such as TP53 was frequently deregulated in BC and the tumor protein p53 (TP53) was recognized as a tumor suppressor factor for several common tumors (Liao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher expression of TP53 mutation was observed in the high stage of bladder cancer or the MIBC, and lower expression of TP53 mutation in the Ta stage of bladder cancer or the NMIBC. The expression level of TP53 mutation was probably a critical diagnosed biomarker in advanced bladder cancer (Liao et al, 2021).…”
Section: Bladder Cancer Related Genes Were Confirmed By Literature Reviewmentioning
confidence: 99%